The ESM – what is behind the propositions? (Economic and Political Thought, 2015)
The debt crisis revealed serious gaps in the hitherto economic managementsystem of the European Union. First of all, the principles of the Stability andGrowth Pact (SGP) turned out to be completely ineffective, since they didnot prevent the European Union from getting into trouble as a result ofirresponsible fiscal policy. Secondly, it became clear that the euro area had noinstruments for management in a critical situation, which made it impossibleto undertake relevant actions. In May 2010, the EU started to look for ananswer to the question how to overcome the crisis. Special rescue fundswere established to prevent the crisis from spreading all over Europe. In thearticle, the author analyses the quality of the EU decission (at the momentthe decisison was taken) and the potential effectivness of the proposed aidsystem architecture.